The FAO-CIHEAM Interregional Cooperative Research Network on Nuts - Rovira M. (Mediterranean stone pine for agroforestry, 2013)
The FAO-CIHEAM Interregional Cooperative Research Network on Nuts (FAO-CIHEAM Nut Network) was established in 1990, after an expert consultation organized by FAO (REU, RNE and AGPS). Exchange of scientific information, joint applied research, exchange of germplasm and establishment of links between researchers were identified as the main objectives. In 1996, FAO and CIHEAM agreed to co-sponsor the Network. CIHEAM was already involved in fostering research activities on nut trees.
AGROPINE 2011 International Meeting on Mediterranean Stone Pine for Agroforestery, 2011/11/17-19, Valladolid (Spain)